(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
Millennials are hailed as people who embrace modernization and the computerized world system. Most people do not recognize the importance of prolonging our territory by using our imagination and creativity in reality. We can express ourselves by creating signature styles of weaved magazine tubes. Symmetry is something that is the same on both sides. Hanging an elegant piece such as an improvised curtain in your home. We used quantitative research as the research design in this study. The materials we used in our research included five broomsticks, two tubes of glue, two rulers, three red ballpens, three magazines, one bottle of varnish, two brides nylons, and two paintbrushes. The procedures we followed are as follows: use the ruler to draw three lines from the boat and point of these lines, draw other lines to make into a triangle and cut, make a circular motion of the finger using a broomstick and use the glue after, and use a large needle with nylon to curve. Buttons and fully varnished magazine tubes were the content of our survey. A questionnaire was constructed in terms of the concept, structural design, construction materials, and presentation. The concept included originality, functionality, usefulness, and uniqueness. Structural design included aesthetic quality, originality, and cleanliness. Construction material included being economical, durability, availability, and feasibility. The presentation included colorfulness, attractiveness, neatness, and is eye-catching. the respondents of our study were STEM students and teachers. The results showed that the weighted means for STEM students were 10 in terms of concept, 4.5 in terms of structural design (highly acceptable), 4.0 in terms of construction materials, and 4.2 in terms of presentation. The difference between the assessments of STEM students and teachers was not significant, and the model was highly acceptable. This study aimed to develop and evaluate an improvised curtain utilizing old magazines as a home decoration. This study sought to answer the following questions: 1. What is the profile of the STEM students and STEM teachers in terms of 1.1 gender, 1.2 age, and 1.3 highest education attainment? 2. How do STEM students and teachers assessed the level of the acceptability of an improvised curtain utilizing old magazines as home decoration in terms of 2.1 concept, 2.2 structural design, 2.3 construction material, and 2.4 presentation? 3. Is there any significant difference between the assessments of the two groups of respondents in terms of the aforementioned variables?